(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research aims to analyze the influence of Islamic religious education on interest in entrepreneurship among student. By integrating entrepreneurial values contained in Islamic teachings, Islamic religious education has the potential to foster entrepreneurial interest and enthusiasm among the younger generation. This research uses qualitative methods obtained from in-depth interviews with Islamic teachers, parents and education experts. The research results show that there is a positive influence between Islamic religious education and interest in entrepreneurship among Muslim teenagers. However, this influence is moderated by factors such as the teaching methods used, social environment, and support from parents and society. This research provides recommendations for integrating entrepreneurship education in the Islamic curriculum, as well as increasing the involvement of parents and the community in fostering entrepreneurial interest in Muslim youth.